Converting a query to CNF - boolean

I've recently been trying to learn logic, but I've come across a query that I can't do and I'm not quite sure where I'm going wrong. When converting a query to CNF, what do you do when you come to this particular situation?
(a AND NOT(b AND c)) AND (d OR e)
= (a AND NOT b) OR (a AND NOT c) AND (d OR e)
=
How would i re-arrange this to get it into CNF form? Am I doing something completely wrong?
Thanks for your help,
Sean

I use the symbols:
^ for AND
v for OR
~ for NOT
and here is how you can transform your formula in CNF:
(a ^ ~(b ^ c)) ^ (d v e)
= (a ^ (~b v ~c)) ^ (d v e) // DeMorgan: ~(A ^ B) <=> (~A v ~B)
= a ^ (~b v ~c) ^ (d v e)
= CNF
Every clauses are separated by AND and contain only OR. With your syntax it gives:
a AND (NOT b OR NOT c) AND (d OR e)
I hope it helps :)

Related

Why is (a and (not b)) or (a and b) = a?

I reached the end of a pretty long Boolean simplification, where I was supposed to prove that something = a. I reached a point (a and (not b)) or (a and b). Any further reorganization of the equation did not bring me further. But using a Truth tabel I checked to see that (a and (not b)) or (a and b) indeed does equal a. And it does make sense intuitively too, but can you actually use the Laws of Boolean Algebra to turn (a and (not b)) or (a and b) into a?
It makes more sense when you use the simplified notation, * for and, + for or, ~ for not.
(a and b) or (a and (not b)) =
(a*b)+(a*(~b)) =
a*(b+(~b)) =
a*(1) =
a
((a and (not b)) or (a and b)) ... distributive law
<=> (a and (b or not b) ... (b or not b) is alway true
<=> a
Feel free to distribute:
c = (a and ¬b)
(a and b) or c
(a or c) and (b or c)
(a or (a and ¬b)) and (b or (a and ¬b))
distribute again for both the left and right sides:
((a or a) and (a or ¬b)) and ((b or a) and (b or ¬b))
simplify:
(a and (a or ¬b)) and ((b or a) and T)
(a and (a or ¬b)) and (b or a)
simplify again (using the absorption property = x and (x or y) == x):
(a) and (b or a)
and again:
a and (a or b)
== a
(I know this is a bit of the long way around...)

Sublist in common lisp

I have list of lists in my program
for example
(( a b) (c d) (x y) (d u) ........)
Actually I want to add 1 new element in the list but new element would be a parent of all existing sublists.
for example if a new element is z, so my list should become like this
( (z( a b) (c d) (x y) (d u) ........))
I have tried with push new element but it list comes like this
( z( a b) (c d) (x y) (d u) ........)
that I dont want as I have lot of new elements coming in and each element represents some block of sublists in the list
Your help would highly be appreciated.
It sounds like you just need to wrap the result of push, cons, or list* in another list:
(defun add-parent (children parent)
(list (list* parent children)))
(add-parent '((a b) (c d) (x y) (d u)) 'z)
;;=> ((Z (A B) (C D) (X Y) (D U)))
This is the approach that I'd probably take with this. It's just important that you save the return value. In this regard, it's sort of like the sort function.
However, if you want to make a destructive macro out of that, you can do that too using define-modify-macro. In the following, we use define-modify-macro to define a macro add-parentf that updates its first argument to be the result of calling add-parent (defined above) with the first argument and the parent.
(define-modify-macro add-parentf (parent) add-parent)
(let ((kids (copy-tree '((a b) (c d) (x y) (d u)))))
(add-parentf kids 'z)
kids)
;;=> ((Z (A B) (C D) (X Y) (D U)))
For such a simple case you can also use a shorter backquote approach, for example:
(let ((parent 'z) (children '((a b) (c d) (e f))))
`((,parent ,#children)))
If you aren't familiar with backquote, I'd recommend reading the nice and concise description in Appendix D: Read Macros of Paul Graham's ANSI Common Lisp.

boolean algebra simplification provided equation

i have this one
OM5= NOT ( A OR (B AND C)) OR D
i provided i photo of it.
http://i.stack.imgur.com/opS1I.png
I used different calcs that were online and all gave me this result
http://www.wolframalpha.com/input/?i=not+(a+or+b%26%26c)+or+d like the wolframalpha one!
But when i did it with my hand i had different results.
the result was NOT(A) AND ( NOT(B) OR NOT(C) OR D )
NOT ( A OR (B AND C)) OR D
= (NOT A AND NOT (B AND C)) OR D
= (NOT A AND (NOT B OR NOT C)) OR D
= (NOT A AND NOT B) OR (NOT A AND NOT C) OR D
That's it.

Convert function with only AND Boolean operations

I have some function like
(A and ( B or c)) or (D and E and (F or H or R or P )))
and I want to convert that function to function with only and operations (of course if possible)
I find that with DeMorgan's Laws can be done some kind of transformations but I didn't manage to conver this function any ideas ?
I know that function
!(A or B) is equal to function !A and !B
but I could not find the equal function to the one above
The function you mentioned:
!(A or B) = !A and !B
is the same as:
A or B = !(!A and !B)
So let's start by splitting your problem into two parts of ABC and DEFHRP.
(A and (B or C)) = (A and !(!B and !C))
(D and E and (F or H or R or P)) = (D and E and !(!F and !H and !R and !P))
Since these two parts are joined by an 'or', we can apply the equivalence again to get:
!(!(A and !(!B and !C)) and !(D and E and !(!F and !H and !R and !P)))
The key substitution you're looking for is A OR B => !(!A AND !B). Using this you can expand the expression.
a and (b or c)
is the same as
a and not (not b and not c)
You can test it here
And for the more complex one:
d and e and (f or h or r)
is the same as
d and e and not(not f and not h and not r)
which is tested here

Rotate the first argument to a function to become nth

Given a function with at least n arguments, I want to rotate the first argument so that it becomes the nth argument. For example (in untyped lambda calculus):
r(λa. a) = λa. a
r(λa. λb. a b) = λb. λa. a b
r(λa. λb. λc. a b c) = λb. λc. λa. a b c
r(λa. λb. λc. λd. a b c d) = λb. λc. λd. λa. a b c d
And so on.
Can you write r in a generic way? What if you know that n >= 2?
Here's the problem stated in Scala:
trait E
case class Lam(i: E => E) extends E
case class Lit(i: Int) extends E
case class Ap(e: E, e: E) extends E
The rotation should take Lam(a => Lam(b => Lam(c => Ap(Ap(a, b), c)))) and return Lam(b => Lam(c => Lam(a => Ap(Ap(a, b), c)))), for example.
The trick is to tag the "final" value of the functions involved, since to normal haskell, both a -> b and a -> (b->c) are just functions of a single variable.
If we do that, though, we can do this.
{-# LANGUAGE TypeFamilies,FlexibleInstances,FlexibleContexts #-}
module Rotate where
data Result a = Result a
class Rotate f where
type After f
rotate :: f -> After f
instance Rotate (a -> Result b) where
type After (a -> Result b) = a -> Result b
rotate = id
instance Rotate (a -> c) => Rotate (a -> b -> c) where
type After (a -> b -> c) = b -> After (a -> c)
rotate = (rotate .) . flip
Then, to see it in action:
f0 :: Result a
f0 = Result undefined
f1 :: Int -> Result a
f1 = const f0
f2 :: Char -> Int -> Result a
f2 = const f1
f3 :: Float -> Char -> Int -> Result a
f3 = const f2
f1' :: Int -> Result a
f1' = rotate f1
f2' :: Int -> Char -> Result a
f2' = rotate f2
f3' :: Char -> Int -> Float -> Result a
f3' = rotate f3
It's probably impossible without violating the ‘legitimacy’ of HOAS, in the sense that the E => E must be used not just for binding in the object language, but for computation in the meta language. That said, here's a solution in Haskell. It abuses a Literal node to drop in a unique ID for later substitution. Enjoy!
import Control.Monad.State
-- HOAS representation
data Expr = Lam (Expr -> Expr)
| App Expr Expr
| Lit Integer
-- Rotate transformation
rot :: Expr -> Expr
rot e = case e of
Lam f -> descend uniqueID (f (Lit uniqueID))
_ -> e
where uniqueID = 1 + maxLit e
descend :: Integer -> Expr -> Expr
descend i (Lam f) = Lam $ descend i . f
descend i e = Lam $ \a -> replace i a e
replace :: Integer -> Expr -> Expr -> Expr
replace i e (Lam f) = Lam $ replace i e . f
replace i e (App e1 e2) = App (replace i e e1) (replace i e e2)
replace i e (Lit j)
| i == j = e
| otherwise = Lit j
maxLit :: Expr -> Integer
maxLit e = execState (maxLit' e) (-2)
where maxLit' (Lam f) = maxLit' (f (Lit 0))
maxLit' (App e1 e2) = maxLit' e1 >> maxLit' e2
maxLit' (Lit i) = get >>= \k -> when (i > k) (put i)
-- Output
toStr :: Integer -> Expr -> State Integer String
toStr k e = toStr' e
where toStr' (Lit i)
| i >= k = return $ 'x':show i -- variable
| otherwise = return $ show i -- literal
toStr' (App e1 e2) = do
s1 <- toStr' e1
s2 <- toStr' e2
return $ "(" ++ s1 ++ " " ++ s2 ++ ")"
toStr' (Lam f) = do
i <- get
modify (+ 1)
s <- toStr' (f (Lit i))
return $ "\\x" ++ show i ++ " " ++ s
instance Show Expr where
show e = evalState (toStr m e) m
where m = 2 + maxLit e
-- Examples
ex2, ex3, ex4 :: Expr
ex2 = Lam(\a -> Lam(\b -> App a (App b (Lit 3))))
ex3 = Lam(\a -> Lam(\b -> Lam(\c -> App a (App b c))))
ex4 = Lam(\a -> Lam(\b -> Lam(\c -> Lam(\d -> App (App a b) (App c d)))))
check :: Expr -> IO ()
check e = putStrLn(show e ++ " ===> \n" ++ show (rot e) ++ "\n")
main = check ex2 >> check ex3 >> check ex4
with the following result:
\x5 \x6 (x5 (x6 3)) ===>
\x5 \x6 (x6 (x5 3))
\x2 \x3 \x4 (x2 (x3 x4)) ===>
\x2 \x3 \x4 (x4 (x2 x3))
\x2 \x3 \x4 \x5 ((x2 x3) (x4 x5)) ===>
\x2 \x3 \x4 \x5 ((x5 x2) (x3 x4))
(Don't be fooled by the similar-looking variable names. This is the rotation you seek, modulo alpha-conversion.)
Yes, I'm posting another answer. And it still might not be exactly what you're looking for. But I think it might be of use nonetheless. It's in Haskell.
data LExpr = Lambda Char LExpr
| Atom Char
| App LExpr LExpr
instance Show LExpr where
show (Atom c) = [c]
show (App l r) = "(" ++ show l ++ " " ++ show r ++ ")"
show (Lambda c expr) = "(λ" ++ [c] ++ ". " ++ show expr ++ ")"
So here I cooked up a basic algebraic data type for expressing lambda calculus. I added a simple, but effective, custom Show instance.
ghci> App (Lambda 'a' (Atom 'a')) (Atom 'b')
((λa. a) b)
For fun, I threw in a simple reduce method, with helper replace. Warning: not carefully thought out or tested. Do not use for industrial purposes. Cannot handle certain nasty expressions. :P
reduce (App (Lambda c target) expr) = reduce $ replace c (reduce expr) target
reduce v = v
replace c expr av#(Atom v)
| v == c = expr
| otherwise = av
replace c expr ap#(App l r)
= App (replace c expr l) (replace c expr r)
replace c expr lv#(Lambda v e)
| v == c = lv
| otherwise = (Lambda v (replace c expr e))
It seems to work, though that's really just me getting sidetracked. (it in ghci refers to the last value evaluated at the prompt)
ghci> reduce it
b
So now for the fun part, rotate. So I figure I can just peel off the first layer, and if it's a Lambda, great, I'll save the identifier and keep drilling down until I hit a non-Lambda. Then I'll just put the Lambda and identifier right back in at the "last" spot. If it wasn't a Lambda in the first place, then do nothing.
rotate (Lambda c e) = drill e
where drill (Lambda c' e') = Lambda c' (drill e') -- keep drilling
drill e' = Lambda c e' -- hit a non-Lambda, put c back
rotate e = e
Forgive the unimaginative variable names. Sending this through ghci shows good signs:
ghci> Lambda 'a' (Atom 'a')
(λa. a)
ghci> rotate it
(λa. a)
ghci> Lambda 'a' (Lambda 'b' (App (Atom 'a') (Atom 'b')))
(λa. (λb. (a b)))
ghci> rotate it
(λb. (λa. (a b)))
ghci> Lambda 'a' (Lambda 'b' (Lambda 'c' (App (App (Atom 'a') (Atom 'b')) (Atom 'c'))))
(λa. (λb. (λc. ((a b) c))))
ghci> rotate it
(λb. (λc. (λa. ((a b) c))))
One way to do it with template haskell would be like this:
With these two functions:
import Language.Haskell.TH
rotateFunc :: Int -> Exp
rotateFunc n = LamE (map VarP vars) $ foldl1 AppE $ map VarE $ (f:vs) ++ [v]
where vars#(f:v:vs) = map (\i -> mkName $ "x" ++ (show i)) [1..n]
getNumOfParams :: Info -> Int
getNumOfParams (VarI _ (ForallT xs _ _) _ _) = length xs + 1
Then for a function myF with a variable number of parameters you could rotate them this way:
$(return $ rotateFunc $ read $(stringE . show =<< (reify 'myF >>= return . getNumOfParams))) myF
There most certainly are neater ways of doing this with TH, I am very new to it.
OK, thanks to everyone who provided an answer. Here is the solution I ended up going with. Taking advantage of the fact that I know n:
rot :: Int -> [Expr] -> Expr
rot 0 xs = Lam $ \x -> foldl App x (reverse xs)
rot n xs = Lam $ \x -> rot (n - 1) (x : xs)
rot1 n = rot n []
I don't think this can be solved without giving n, since in the lambda calculus, a term's arity can depend on its argument. I.e. there is no definite "last" argument. Changed the question accordingly.
I think you could use the techniques described int the paper An n-ary zipWith in Haskell for this.
Can you write r in a generic way?
What if you know n?
Haskell
Not in plain vanilla Haskell. You'd have to use some deep templating magic that someone else (much wiser than I) will probably post.
In plain Haskell, let's try writing a class.
class Rotatable a where
rotate :: a -> ???
What on earth is the type for rotate? If you can't write its type signature, then you probably need templates to program at the level of generality you are looking for (in Haskell, anyways).
It's easy enough to translate the idea into Haskell functions, though.
r1 f = \a -> f a
r2 f = \b -> \a -> f a b
r3 f = \b -> \c -> \a -> f a b c
etc.
Lisp(s)
Some Lispy languages have the apply function (linked: r5rs), which takes a function and a list, and applies the elements of the list as arguments to the function. I imagine in that case it wouldn't be so hard to just un-rotate the list and send it on its way. I again defer to the gurus for deeper answers.